Improvement of mechanical property for BNNSs/PAN composite films via electro-spinning with high filtration performance. (11th November 2022) - Zhou, Yingying; Sun, Runjun; Wang, Ruining
People increasingly need air filters with ultra-high efficiency due to air pollution. In this work, BNNSs (boron nitride nanosheets) were prepared by chemical method using potassium permanganate and sulphuric acid. This functionalization induced the exfoliation of the layered structure of h-BN into monolayer or few-layer sheets. Infrared spectrum analysis shows that the oxidation functional group was introduced into hexagonal boron nitride. Further investigation of the crystallization property was accomplished by XRD analysis in conclusion that the crystal structure was not changed for the introduction of oxidation functional group. The polyacrylonitrile (PAN) and BNNSs/PAN nanofiber films were constructed by electrospinning. It is found that the electrospun nanofiber films had good filtration effect and could capture the most particles in the air because of electrostatic adsorption. The removal rate of particle by the filters reached 99.8% for BNNSs/PAN nanofiber films. Addition of BNNSs increaed the mechanical property of the nanofiber films.